BOOK REVIEWS (Journal of Finance, 1969)
Book reviewed in this article: Aggregate Theory and Policy: MacroEconomic Theory: A Mathematical Treatment . By R. G. D. A llen . Aggregate Theory and Policy: acroeconomic Theory and Stabilization Policy . By J ohn M. C ulbertson . Aggregate Theory and Policy: Economic Planning and Policies in Britain, France and Germany . By M alcolm M ac L ennan , M urray F orsyth and G eoffrey D enton . Aggregate Theory and Policy: The Job Content of the U.S. Economy, 1940–1970 . By J ames G. S coville . Aggregate Theory and Policy: Readings in the Modern Theory of Economic Growth . Edited by J oseph E. S tiglitz and H irofumi U zawa . Aggregate Theory and Policy: 4 Monetary Policy for Latin America . By P ierre U ri , together with N icholas K aldor , R ichard R uggles , and R obert T riffin . Aggregate Theory and Policy: lue, Capital, and Growth: Papers in Honour of Sir John Hicks . Edited by J. N. W olfe . Business Finance and Investments: Risk and Uncertainty: Proceedings of a Conference Held by the International Economic Association . Edited by K arl B orch and J an M ossin . Business Finance and Investments: Personal Trust Investment Management . C. F. A. R esearch F oundation (Monograph Series Number 2). Business Finance and Investments: Managerial Finance . By S alomon J. F link and D onald G runewald . Business Finance and Investments: Theory of Valuation . By C harles L. H ubbard and C lark A. H awkins . Business Finance and Investments: Business Combinations: Planning and Action . By A rthur . W yatt and D onald E. K iesos . Business Finance and Investments: Capital Budgeting: The Economic Evaluation of Investment Projects . By W illiam H. J ean . Business Finance and Investments: The Cost of Capital . By W ilbur G. L ewellen . Business Finance and Investments: Measuring the Investment Performance of Pension Funds for the Purpose of Inter‐Fund Comparison . By J ames L orie Business Finance and Investments: Decision Analysis: Introductory Lectures on Choices Under Uncertainty . By H oward R aiffa . Business Finance and Investments: Guide to Convertible Securities . By W illiam S chwartz and J ulius S pellman . Business Finance and Investments: Corporation Finance, Policy, Planning, Administration . By P aul M. V an A rsdell . Financial Institutions and Markets: Competition and Controls in Banking . By D avid A. A lhadeff . Financial Institutions and Markets: Investment Banking and the New Issues Market . By I rwin F riend , J ames R. L ongstreet , M orris M endelson , E rvin M iller , and A rleigh P. H ess , J r . Financial Institutions and Markets: The New York Money Market and the Finance of Trade, 1900–1913 . By C. A. E. G oodhart . Financial Institutions and Markets: A Study of Wholesale Banking Behavior . By N eil B. M urphy . Financial Institutions and Markets: The Organization of Industry . By G eorge J. S tigler . Financial Institutions and Markets: Mutual Savings Banks: The Evolution of a Financial Intermediary . By W eldon W elfling . International Finance: Financial Capital Flows in the U.S. Balance of Payments . By W illiam H. B ranson . International Finance: Readings in the Euro‐Dollar . Edited by E ric C halmers . International Finance: American Business Abroad: Six Lectures on Direct Investment . By C harles P. K indleberger . International Finance: Toward an Orderly Market: An Intensive Study of Japan's Voluntary Quota in Cotton Textile Imports . By J ohn L ynch . Public Finance: Nigerian Federal Finance . By A debayo A dede ji . Public Finance: Governmental Problem‐Solving: A Computer Simulation of Municipal Budgeting . By J ohn P. C recine . Public Finance: Budgeting Public Funds: The Decision Process in an Urban School District . By D onald G erwin . Public Finance: State and Local Tax Problems . Edited by H arry L. J ohnson . Public Finance: Public Expenditures in Communist and Capitalist Nations . By F rederic L. P ryor . Public Finance: The Metropolitan Enigma: Inquiries into the Nature and Dimensions of America's “Urban Crisis.” Edited by J ames Q. W ilson .